Combinações afins - Sousa, Francisco José Calixto de (2013)
In this paper, we consider combinations of related vectors of a vector space with special applications in high school through the weighted arithmetic mean and the Jensen inequality. We observed characteristics of specific sets of linear transformations in the vector spaces as convex sets and related varieties through the core and image transformations. Established relations between affine transformations, combinations thereof and linear transformations. We discuss the size of the hyperplane relating it as affine variety. We see that all of Rn vector subspace with dimension n - 1 is a hyperplane, as the core of a linear functional.